Natural Occurrence of Beauveria bassiana (Balsamo) Vuillemin (Hyphomycetes: Moniliales) on Anticarsia gemmatalis Hübner (Lepidoptera: Noctuidae) in the State of Mato Grosso do Sul - Rossoni, Camila; Kassab, Samir Oliveira; Barbosa, Rogério Hidalgo; Silva, Antonio Souza; Mota, Thiago Alexandre; Loureiro, Elisângela de Souza (EntomoBrasilis, 2013)
Natural occurrence of an entomopathogenic fungus was reported on Anticarsia gemmatalis Hübner (Lepidoptera: Noctuidae) in an area planted with conventional soybeans located in Dourados, Mato Grosso do Sul, Brazil. The caterpillar was collected in the field and taken to the microbiology laboratory of the Universidade Federal da Grande Dourados (UFGD) where it remained in a moist chamber for approximately 7 days. Later, the fungus was isolated on culture medium (PDA) for identification of the entomopathogenic species. The fungus was identified as Beauveria bassiana (Balsamo) Vuillemin (Hyphomycetes: Moniliales) and this represents the first record of parasitism of this species on the soybean caterpillar in the state of Mato Grosso do Sul. Ocorrência Natural de Beauveria bassiana (Balsamo) Vuillemin (Hyphomycetes: Moniliales) Sobre Anticarsia gemmatalis Hübner (Lepidoptera: Noctuidae)no Estado de Mato Grosso do Sul Resumo. Relata-se a ocorrência natural de um fungo entomopatogênico sobre a lagarta Anticarsia gemmatalis Hübner (Lepidoptera: Noctuidae) em uma área de soja convencional situada no município de Dourados, Mato Grosso do Sul. A lagarta foi coletada a campo e levada ao laboratório de microbiologia da Universidade Federal da Grande Dourados (UFGD), onde permaneceu em câmera úmida por aproximadamente 7 dias. Posteriormente, o fungo foi isolado em meio de cultura (BDA) para identificação da espécie do entomopatógeno. O fungo foi identificado como Beauveria bassiana (Balsamo) Vuillemin (Hyphomycetes: Moniliales) e, isso representa o primeiro registro de parasitismo, dessa espécie, sobre a lagarta-da-soja no Estado de Mato Grosso do Sul.